ANTI DEPRESSANTAND ANTIOXIDANT ACTIVITY OF METHANOLIC EXTRACT OF ASPARAGUS RACEMOSUS SEEDS - K.SRAVANI; KRISHNA, K.SIVARAMA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective: Asparagus Racemosushas been referred in Indian traditional medicine system (Ayurveda) for treatment of various diseases. In the present study extracts of Asparagus Racemosusstudied for its antidepressant activityin animal models of depression and invitro antioxidant activity.[1] Materials and methods: Methanolic extracts of complex product prepared from dried seeds ofplantAsparagus Racemosus. In the present study, the antidepressant effect of Asparagus Racemosuswas examined using two behavioural models, the forced swim test (FST) in rats and tail suspension test (TST) in mice and one invitro model such as estimation of Dopamine levels in rat brain[2].DPPH & Nitric oxide radical scavenging activity models were selected for antioxidant activity. Results: The invitroantioxidant studies such as DPPH activity and Nitric oxide radical scavenging activity shows the satisfactory results, the concentration of extract increases the percentageÂ inhibition of DPPH and Nitric oxide radical scavenging activity also increases, so they shows the Dose dependent action.InForcedSwimTest&TailSuspensionTest demonstratedadosedependant, statistically significantreductioninduration ofimmobility that was comparable to Imipramine (20mg/kg). Conclusion: Theeffectof200mg/kg of Asparagus Racemosus wasbetterthan20 mg/kg Imipramine. Theeffectof100mg/kgof AGM wassignificantwhencomparedtovehicletreatedgroup. In in-vitro study, Asparagus Racemosusin the doses of 100mg/kg and 200mg/kg showed increased levels of Dopamine when compared to that of normal. Plant extract at dose of 200 mg/kg showed increased levels of Dopamine, which is nearly equal to that of Standard. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Keywords:AsparagusRacemosus,Antioxidant,Antidepressant ,Methanolic extract